2015
DOI: 10.1097/aog.0000000000000874
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free DNA Analysis in Maternal Plasma in Cases of Fetal Abnormalities Detected on Ultrasound Examination

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 16 publications
4
47
1
1
Order By: Relevance
“…The test performance was similar in the 2 laboratories -mainly so for trisomy 21, since there was no falsenegative result in either laboratory for trisomy 21, which is consistent with the very high performance of cfDNA testing in the detection of trisomy 21 at both laboratories in high-and low-risk populations [4][5][6][7][8][9]21]. The detection rates for trisomy 18/13 were also high, as reported previously [8,29,30], but the numbers were too small to draw definitive conclusions.…”
Section: Performance Of the Cfdna Test In Each Laboratorysupporting
confidence: 69%
See 4 more Smart Citations
“…The test performance was similar in the 2 laboratories -mainly so for trisomy 21, since there was no falsenegative result in either laboratory for trisomy 21, which is consistent with the very high performance of cfDNA testing in the detection of trisomy 21 at both laboratories in high-and low-risk populations [4][5][6][7][8][9]21]. The detection rates for trisomy 18/13 were also high, as reported previously [8,29,30], but the numbers were too small to draw definitive conclusions.…”
Section: Performance Of the Cfdna Test In Each Laboratorysupporting
confidence: 69%
“…In another study involving 892 patients with 113 cases of trisomy 21, 18, or 13, Benachi et al [21] reported detection rates of 100% for trisomy 21 and 13 and 88% for trisomy 18. What is interesting in this study is that in 5 patients with abnormal results, the FF was < 4%; yet the Zscore was highly suggestive of aneuploidy, and therefore the results were confirmed by karyotyping.…”
Section: Performance Of the Cfdna Test In Each Laboratorymentioning
confidence: 99%
See 3 more Smart Citations